Financial Performance Evaluation of PT. Telekomunikasi Indonesia, Tbk. and PT. Indosat, Tbk. - Wendra Hartono; Gracia Ongkowijoyo (Accounting Study Program, Universitas Ciputra Surabaya, 2019)
Two telecommunications companies in Indonesia have their names listed in Indonesian Stock Exchange (IDX) namely, PT. Indosat, Tbk. (ISAT) and PT Telekomunikasi Indonesia (TLKM) have enlivened the telecommunication industry. This study aims to evaluate the performance of two telecommunications companies in Indonesia by assessing, comparing and analyzing fundamentally, technically and news or company policies occurred in the field during 2017 - May 2018. In Fundamental Analysis, the two companies are categorized as companies that have a good financial condition. However, in the second semester of 2017, telecommunication companies experienced a significant decline in market value, which was contrary to the fundamental analysis. If viewed from a technical perspective, this telecommunication service company has good prospects for the future. Company policy or news is also one of the determining factors for the increase or decrease in stock prices. The overall results of the study concluded that TLKM shares have a fundamental, and technical, that is better than ISAT, while news and company policies can be investors' supporting data in determining stock purchases.